Formulasi dan Aktivitas Tablet Kunyah Carica papaya L. dan Morinda citrifolia L sebagai Hepatoprotektor selama pengobatan Tuberculosis (TBC) - Sunarni, Titik; Prastiwi, Rini; Kuncahyo, Ilham; Mardiyono, .; Rinanto, Yudi (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Formulation of chewable tablets of ethanolic extracts of Carica papaya L leaves and Morinda citrifolia L fruits and investigation of the activity towards liver damage induced by tuberculosis drugs has been performed. The rats were devide into six groups. The normal control without any treatment, negatif control were given INH 10 mg/200g-RIF 10 mg/200g, positif control were given INH-RIF and methicol, and the treatment group were given INH-RIF with chewable tablets of papaya extracts 120mg/200g and morinda extracts 20mg/200g of three tablets formula with PVP 1%, 3% and 5%. Each group were treated every day for 27 days. The measuring to monitor bilirubin serum, ALT and AST levels on 0,14th, 21st and 28th day. The study showed that the group that given chewable tablets of combination of papaya extract 120mg/200g and morinda extract 20mg/200g can prevent the occurrence of liver necrosis with necrosis value of 19,92% (PVP 3%) and 19,90 (PVP1%), compared to the negative control of 41.78% as well as reducing the value of ALT, AST and bilirubin. The tablet formula that can be received on the best of taste and most effective as hepatoprotektor is the chewable tablet with PVP 3%.Keywords : Hepatoprotector, Carica papaya L., Morinda citrifolia L., Isoniazid, Rifampicin